Indexing of Iranian Publications in Well-known Endodontic Textbooks: A Scientometric Analysis - Kakooei, Sina; Mostafavi, Mahshid; Parirokh, Masoud; Asgary, Saeed (Iranian Endodontic Journal, 2016)
Introduction: Quoting an article in well-known textbooks is held as a credit for that paper. The numbers of Iranian publications mentioned in endodontic textbooks have increased during recent years. The aim of this investigation was to evaluate the number of Iranian articles quoted in eminent endodontic text books. Methods and Materials: Three known textbooks (Ingle’s Endodontics, Seltzer and Bender’s Dental Pulp and Cohen’s Pathways of the Pulp) were chosen and all the editions of the textbooks since 2000 were investigated for quoted Iranian publications. Only Iranian authors with affiliations from a domestic university were chosen. All references at the end of each chapter were read by hand searching, and results were noted. The trend and percentage of Iranian publications in different editions of the textbooks were also calculated. The number of citations of these publications in Google Scholar and Scopus databases were also obtained. Results: The number of Iranian publications in all well-known textbooks have notably increased since 2000. The number and percentage of Iranian publications in the latest edition of Cohen’s Pathways of the Pulp was higher compared to other textbooks as well as the previous edition of the same text. Conclusion: Number and percentage of Iranian publications in the field of endodontics in all three textbooks have remarkably increased since 2000. Keywords: Dental Pulp; Endodontics; Index; Ingle; Iranian Publications; Pathways of the Pulp; Quote; Scientometric; Textbooks